2020
DOI: 10.1002/er.4945
|View full text |Cite
|
Sign up to set email alerts
|

How to select regenerative configurations of CO 2 transcritical Rankine cycle based on the temperature matching analysis

Abstract: Summary CO2 transcritical Rankine cycle is regarded as a potential technology for internal combustion engines waste heat recovery, and its regenerative configurations present great prospect to increase the power output capacity. This paper proposed different regenerator layout configurations based on the temperature matching analysis, including low temperature regenerative transcritical Rankine cycle (LR‐TRC), high temperature regenerative transcritical Rankine cycle (HR‐TRC), dual regenerative transcritical R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Sánchez and Silva 29 indicated the size of a heat exchanger (namely evaporator and condenser) can be reduced by a recuperator. Tian et al 30 indicated a high impact of regenerative configurations on improving net power output, especially for split dual regenerative TRC. However, Ramy et al 31 indicated the recuperator had negative effects on compactness and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez and Silva 29 indicated the size of a heat exchanger (namely evaporator and condenser) can be reduced by a recuperator. Tian et al 30 indicated a high impact of regenerative configurations on improving net power output, especially for split dual regenerative TRC. However, Ramy et al 31 indicated the recuperator had negative effects on compactness and performance.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, a split dual regenerative transcritical Rankine cycle (SR-TRC) is investigated shown in Figure 1. Due to the design of split branches and two regenerators, the SR-TRC system can meet the requirement of recovering the jacket water and exhaust gas simultaneously and improve the temperature matching in the whole heat absorption process, and has been proved to be a novel cycle configuration to achieve better temperature match between the system and heat sources [36]. The concrete working process of SR-TRC is: the working fluid transferring heat from jacket water in the preheater (2-3) is split into two parts, namely, high-temperature branch (H-branch) and low-temperature branch (L-branch).…”
Section: Trc Configurationmentioning
confidence: 99%